Revisiting Late Pleistocene glacier dynamics north-west of the Feldberg, southern Black Forest, Germany - F. M. Hofmann; F. Rauscher; W. McCreary; J.-P. Bischoff; F. Preusser (E&G Quaternary Science Journal, 2020)
The southern Black Forest was temporarily covered by a ∼1000 km 2 large ice cap during the Late Pleistocene. However, during the last glaciation maximum in the Alps the atmospheric circulation over Europe was presumably characterised by the advection of humid air masses from the Mediterranean Sea. As a consequence, the ice cap of the Black Forest was likely in a leeward position due to its location north of the Alps. This raises the question of whether it reached its last maximum extent simultaneously with the glaciers in the Alps. As modern dating techniques have hitherto not been applied to the southern Black Forest, the timing of the last local glaciation maximum remains poorly constrained. As a first step towards an independent regional glacier chronology, we present a critical re-examination of glacial landforms in the area north-west of the highest summit of the Black Forest (Feldberg, 1493 m a.s.l.). It relies on both the analysis of remote sensing data and field mapping. The review of previous studies highlights important disagreements regarding the location of ice-marginal positions and their correlation. In addition, our findings challenge earlier studies on the glaciation of the Black Forest: some previously described ice-marginal positions could not be confirmed, whereas some of the newly identified moraines are described for the first time. This highlights the need for detailed geomorphological investigations prior to the application of geochronological methods. A multi-ridged series of terminal moraines in one of the studied valleys, Sankt Wilhelmer Tal, is proposed as the main target for future dating. Due to discrepancies with earlier studies, future efforts should reinvestigate other key areas related to the last glaciation of the southern Black Forest.